Perceptions of principals and circuit managers on the need for school social workers at Mankweng Circuit, South Africa - Sibise, Katekani (My University, 2021)
The need for school social work was first recognised in the 1940s in South Africa. And in recent years, researchers have shown interest in understanding social workers in school settings. In pursuit of adding to knowledge, the researcher undertook a study to look at the perceptions of school principals and circuit managers on the need for school social workers in Mankweng, Limpopo province. The ecological theory by Bronfenbrenner laid the foundation for this research. The study was driven by a qualitative methodology and a descriptive design; where ten (10)participants were selected purposefully and interviewed in Mankweng, Polokwane. The interviews were semi-structured and used an interview guide. The thematic content analysis method was considered to make sense of the data gathered through interviews and observations. The study post analysis found that in schools, learners encounter hurdles, social workers play diverse roles, and those social workers are a prerequisite in school settings. In the light of these findings, the researcher came to recommendations that: government should employ and place social workers in all public schools, and that the South African Council for Social Service Profession should promote more specialisation of school social workers to defeat social problems in our schools.
Thesis (M.A. (Social Work)) -- University of Limpopo, 2021
Keywords: School social work; Circuit managers; Principals; School principals; Social workers -- South Africa -- Limpopo; Social service -- South Africa -- Limpopo